Intellectual Capital Reporting and Cost of Debt - Phurahong, Natthaporn; Nachairit, Ingorn; Nilniyom, Natnapha; Wongkhae, Komkrit (วารสารการบัญชีและการจัดการ, 2023)
This study, which is the first longitudinal study of intellectual capital reporting in Thailand, aims to investigate the relationship between intellectual capital reporting and the cost of debt. A sample of 296 firm-year observations were selected from listed companies in the Market for Alternative Investment of Thailand from 2015 to 2019. Drawing on secondary data, this study applied descriptive analysis, correlation matrix, and panel data analysis. Moreover, intellectual capital reporting was measured by the Modified-Value Added Intellectual Coefficient (M-VAIC) and the number of words, including the cost of debt was measured by the financial expenses. The results showed that intellectual capital reporting, derived from both financial and non-financial information, is statistically significant and negatively correlated with the cost of debt. The findings demonstrate that intellectual capital reporting is useful to mangers of borrowing firms as it helps them to get a lower cost of debt and useful to lenders because they have better understanding financial position. Signaling theory was used to confirm that intellectual capital reporting made by firms can reduce information asymmetry between the two parties. The study highlights that listed firms on the Market for Alternative Investment of Thailand, as debt financing is important initiation for supporting financial structure, should focus on intellectual capital performance and disclosure allowing lenders to assess the